A indissociabilidade entre gênero, classe e etnia para a compreensão da situação da mulher na sociedade de classes contemporânea e a necessidade de um feminismo para os 99%: https://doi.org/10.53809/TS_ISS_2022_n.2_54-68 ("Temas Sociais" Journal, 2022)
This article is the result of a bibliographical review of the works of Heleieth Saffioti, comparing them with the Feminist Manifesto of Cinzia Arruzza, Tithi Bhattacharya and Nancy Fraser. Such analysis intends to answer the question: is it possible to overcome gender violence, attending to the demands of the exploited classes, separating it from the issues of class and ethnicity? It is assumed that, in order to meet the needs of the exploited populations, the inseparability of the categories gender, class, and ethnicity must be taken into account. The objective of this article is to analyze these categories as inseparable issues for the construction of a feminism that contemplates the needs of the exploited classes in contemporary capitalism. To carry out this reflection, this article is based theoretically and methodologically on dialectical historical materialism, that is, it analyzes concrete reality, describing it theoretically, in order to understand it in its multiple determinations.